UTILIZATION OF TIO₂ IMPREGNATED ZEOLIT-ZSM-5 TO DECREASE CONCENTRATION OF CR (VI) IN SOLUTION AT pH VARIANCE - Siska Nurprihandayani; Stalis Norma Ethica; Ana Hidayati Mukaromah (Universitas Muhammadiyah Semarang, 2018)
Chromium (VI) or Cr (VI) is one of heavy metal ions, which presence in the environment comes from industrial waste water disposal such as metallic coating, leather tanning and paint industry. Cr (VI) ions are toxic as they could cause lung cancer, chronic infection and polyps. An effort to decrease Cr (VI) concentration has been done by using TiO₂ impregnated Zeolite ZSM-5 (TiO₂-ZSM-5) at 1,25% w/v concentration with pH variation within 75-minute of UV exposure time. This study aims to investigate the effect of pH variation after addition of TiO₂- ZSM-5 powder on Cr (VI) solution, in a way to reduce the presence of the toxic ions in its solution. Object of this study was Cr (VI) solution at concentration of 50 mg/L. The evaluation was carried out on Cr (VI) solutions as samples including vontrol after adding Zeolite ZSM-5 alone, TiO₂ alone and TiO₂ impregnated Zeolite ZSM5 powder. Data analysis was carried out statistically using One-way Annova.The results showed that initial Cr (VI) concentration was 49,73 mg/L and the percentages of Cr (VI) decrease at pH 2, 4, 6, 8 and 10 respectively were 37,55; 34,72; 25.88; 18,10; 11.11%. It means that the highest percentage of Cr (VI) concentration decrease was at pH 2. Based on the statistical analysis results (p value 0,000), the most significant effects in the decreaseof concentation of Cr (VI) solution used in this study were shown by the addition of TiO₂-ZSM-5 powder and by addition of H+ ion (causing pH=2) into the used solution. As conclusion, treatment using TiO₂ impregnatedZeolite ZSM-5 at pH 2 is potential to be used as a way to handle water pollution caused by Cr (VI).